Why is Micro Segmented Flow Particularly Promising for the Synthesis of Nanomaterials?. Issue 6 (29th May 2013) - Köhler, J. M.; Li, S.; Knauer, A.; Hessel, Volker; Wang, Qi
Abstract The particular advantages of micro segmented flow are discussed with respect to the specific requirements in the synthesis of nanoparticles. Compartimentation of a liquid, slug‐flow transport behavior, decoupling between reaction solution and wall, and induction of a fast radial mass and heat transfer by flow‐induced segment‐internal convection are the most important aspects for realizing a focussed nucleation and homogeneous particle growth under micro continuous‐flow conditions. In addition, the micro fluid‐segment technique allows the automated realization of large parameter studies and combinatorial investigations by a simple flow rate variation. Beside some concepts of process design, examples for the synthesis of ZnO micro‐ and nanoparticles as well as for plasmonic nanoparticles are given in order to demonstrate the power of micro segmented flow for generation of nanoparticles of high homogeneity and for tuning of particle properties.